(Invited) Robust and Active Mixed-Conducting Electrodes for Intermediate-Temperature Fuel Cells. (31st August 2017) - Chen, Yu; Chen, Dongchang; Ding, Dong; Liu, Meilin
Abstract : Intermediate-temperature solid oxide fuel cells are ideally suited for distributed generation (which may be integrated with smart grids). To make these fuel cells economically competitive and commercially viable, however, several materials challenges must be overcome. One of them is the creation of durable, low-cost cathode materials and nanostructures of high electro-catalytic activity for oxygen reduction reaction at intermediate temperatures. Here we report our findings in the development of an effective approach to fabrication of high-performance catalyst-coated electrodes of dramatically enhanced electrocatalytic activity and durability. The concept of modifying electrode surface through solution infiltration of a catalyst to create unique hybrid electrode structures (e.g., exsoluted nanoparticles on a conformal coating) are readily applicable to other electrochemical energy storage and conversion systems, including metal-air batteries, supercapacitors, and electrolyzers.